Cardiovascular safety of febuxostat and allopurinol in patients with gout: A meta-analysis - Guan, Xudong; Zhang, Shengzhao; Liu, Jiayan; Wu, Fengbo; Zhou, Lingyan; Liu, Ying; Su, Na (Frontiers in Pharmacology, 2022)
Background: Gout is a common disease and usually treated with uric-acid-lowering drugs (the most commonly used of which are febuxostat and allopurinol). However, the cardiovascular safety of febuxostat and allopurinol is still controversial. The purpose of our study is to evaluate the cardiovascular safety of the two drugs in patients with gout by reconstructed individual-patient data level meta-analysis. Methods: PubMed, Embase, CBM, CNKI, Wan fang, Central and VIP were searched from their earliest records to January 30th 2022. Randomized controlled trials which evaluated the cardiovascular safety of febuxostat or allopurinol for treating patients with gout were included. Based on the Kaplan-Meier curves of the two studies, individual patient data (IPD) were extracted and reconstructed. We used time-varying risk ratios (RRs) to summarize time-to-event outcomes and the RRs of MACE incidence, cardiovascular mortality, and all-cause mortality were calculated by multi-level flexible hazard regression model in 1-stage meta-analyses. P values were calculated by log-rank test. At the same time, using the reconstructed IPD, we did 2-stage meta-analyses to inform the quantitative estimates of time-specific relative risks at the 6 time points (1 year, 2 years, 3years, 4 years, 5 years and 6 years) based on random effects model. Results: Two RCTs with 12318 participants were included. In the incidence of major adverse cardiovascular events between the two regimens，there was no significant difference [RR=0.99 (95%CI, 0.89-1.11), P=0.87]; At the same time, there was no significant difference in cardiovascular mortality [RR=1.17 (95%CI, 0.98-1.40)，P=0.08] or all-cause mortality [RR=1.03 (95%CI, 0.91-1.17)，P=0.62]. In terms of 2-stage meta-analyses, there was no significant difference in any outcomes at any time points (moderate- to low-certainty evidence). Conclusion: In patients without atherosclerotic disease, febuxostat likely has a similar cardiovascular profile to allopurinol. However, in patients with a history of cardiovascular disease, allopurinol treatment is associated with less cardiovascular mortality as compared with febuxostat.